Virtual reality puzzle game - Kuan, Ji Jie (2019)
There are many use case scenarios which employ the use of Virtual Reality (VR). In particular, a VR game can be used to provide insight into various facets of human behaviour. This project demonstrates how a convincing VR environment can be easily created using Unity3D with the SteamVR plugin. This paper documents the considerations and development of a VR puzzle game with six unique puzzle rooms. The player will have to accomplish a task in each room before being allowed to progress to the next room. In addition, the development of the puzzle game incorporates important game design principles to better appeal to the target audience. To provide for extensibility, the VR game comes equipped with a scoring feature to measure the performance of the player. The score can be acted upon by industries employing the use of VR to provide feedback to the player.